Mapping Manila Transit : A New Approach to Solving Old Challenges - Krambeck, Holly (World Bank Group, Washington, DC, 2015)
Whether they attempt to build jeepney stops, expand transit access, or improve bus routes, transit projects across much of the developing world are often hampered by (1) the lack of accurate transit maps and data and (2) the weak capacity of transit agencies to acquire and use such data. To address the twin aspects of this long-standing challenge, the World Bank, in collaboration with the Philippines and Australian Aid, developed both a methodology and a suite of open-source software applications based on free, internationally supported open data standards. The solutions have allowed the quick, low-cost production of transit maps; and they have empowered the agencies, and potentially businesses and the rest of government, for the first time to make ambitious planning and investment decisions based on accurate, comprehensive transit data. The global applicability of this approach has been demonstrated by its adoption in six other developing countries to date.